2007
DOI: 10.1038/nature05533
|View full text |Cite
|
Sign up to set email alerts
|

Ultralow-power organic complementary circuits

Abstract: The prospect of using low-temperature processable organic semiconductors to implement transistors, circuits, displays and sensors on arbitrary substrates, such as glass or plastics, offers enormous potential for a wide range of electronic products. Of particular interest are portable devices that can be powered by small batteries or by near-field radio-frequency coupling. The main problem with existing approaches is the large power consumption of conventional organic circuits, which makes battery-powered appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

22
1,094
3
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 1,371 publications
(1,122 citation statements)
references
References 24 publications
22
1,094
3
3
Order By: Relevance
“…1a), which resemble a known and well-modeled device, the ultra-thin MIS that was investigated with SiO 2 as insulator. Remarkably, an MIS structure with an alkyl monolayer insulator shows reproducibility and uniformity that are superior to what is obtained with inorganic oxides of similar width [40,56] and for which, even if the alkyl monolayer width is shrunk down to a C 1 (ÀCH 3 ) layer, MIS-like behavior persists. [19,20] The dielectric strength of alkyl monolayers on either Si [57,58] or Au [59] is about 10-20 MV cm À1 , twice that of bulk SiO 2 , [41] 10 times that of bulk polyethylene, [57] and comparable to that of alkyl monolayers on SiOx.…”
Section: Why Alkanes? Insulating Versus Conjugated Moleculesmentioning
confidence: 91%
See 1 more Smart Citation
“…1a), which resemble a known and well-modeled device, the ultra-thin MIS that was investigated with SiO 2 as insulator. Remarkably, an MIS structure with an alkyl monolayer insulator shows reproducibility and uniformity that are superior to what is obtained with inorganic oxides of similar width [40,56] and for which, even if the alkyl monolayer width is shrunk down to a C 1 (ÀCH 3 ) layer, MIS-like behavior persists. [19,20] The dielectric strength of alkyl monolayers on either Si [57,58] or Au [59] is about 10-20 MV cm À1 , twice that of bulk SiO 2 , [41] 10 times that of bulk polyethylene, [57] and comparable to that of alkyl monolayers on SiOx.…”
Section: Why Alkanes? Insulating Versus Conjugated Moleculesmentioning
confidence: 91%
“…For most metals (except the most noble ones, Au and Pt) and compound semiconductors, residual surface oxides are inevitable and fairly unstable, also because of the rich binding chemistry of surface oxides and hydroxides. [37,38] While that same chemistry can be put to good use in molecular electronics (e.g., silanes on SiOx, [39] phosphonates on Al 2 O 3 [40] and GaAs [36] ), below a minimal oxide width the reproducibility and stability of an oxidized surface is poor. An electronically ill-defined oxide also complicates junction modeling.…”
Section: Why Silicon? Semiconducting Versus Metallic Electrodesmentioning
confidence: 99%
“…For example, although excellent mobilities have been observed with molecular metal chalcogenide complexes 18,19 , these NCs are dissolved in hydrazine, an extremely caustic solvent that is not compatible with flexible plastics. In addition, as a wide range of flexible electronic applications are typically powered by small thin-film batteries or radio frequency fields 22,23 , it is necessary to show the scalability of these colloidal inks to minimize energy consumption. We recently demonstrated low-voltage operation of flexible colloidal nanowire FETs using thin Al 2 O 3 as our robust, high capacitance and low-leakage gate dielectric material compatible with plastics 24 .…”
mentioning
confidence: 99%
“…9,13 Theoretical work has shown that DIBL in short-channel SWCNT FETs can be reduced by implementing a double-gate, triple-gate, or surround-gate device structure. 17 Combining patterned bottom gate electrodes 12 with a thin, SAM-based gate dielectric 16 offers a number of advantages. First, it allows the integration of individually addressable, low-voltage transistors into large-scale integrated circuits on arbitrary substrates, including glass or flexible plastics, which is not possible with a global, unpatterned gate (and hence not possible with a SiO 2 dielectric that is thermally grown on a doped silicon wafer).…”
mentioning
confidence: 99%
“…Pentacene thin-film transistors (TFTs) show excellent initial performance with carrier mobility around 1 cm 2 /Vs, transconductance exceeding 40 µS/mm, subthreshold swing of 100 mV/decade, and on/off ratio of 10 7 or greater. 16 But pentacene is readily oxidized in the presence of ambient species, yielding molecules such as 6,13-pentacenequinone, which act as charge traps or scattering sites in the semiconductor. 27 Consequently, the transconductance of pentacene transistors exposed to air decays rapidly and significantly.…”
mentioning
confidence: 99%